Pengembangan Model Edutourism Di Pertanian Terpadu Bukit Tursina, Bogor - Goenadhi, Felix; Komalasari, Farida; Kumar, Suresh; Witono, Aloysius Bambang Memet (Lentera Ilmu Madani, 2024)
The Community Service Program (PkM) at Bukit Tursina Integrated Agriculture aims to develop the area into an edutourism destination based on sustainable integrated agriculture. With an environmentally friendly approach, Bukit Tursina is a food production center and an educational model for sustainable agricultural and livestock practices. This initiative is designed to enhance the community’s skills in managing educational tourism, encourage active involvement from local communities, and create interactive learning experiences for visitors. The methods used include initial observations, needs analysis, area development planning, the creation of educational modules, tour guide training, and pilot testing of the edutourism program. Additionally, the program involves structuring the tourism area, installing educational elements, and implementing social media promotional strategies. The expected outcomes of this program include improving the community’s capacity to manage educational tourism professionally, increasing the number of visitors, and raising awareness of sustainable agricultural practices.